Variability of internal and external loads and technical/tactical outcomes during small-sided soccer games: a systematic review - Clemente, Filipe; Aquino, Rodrigo; Praça, Gibson Moreira; Rico-González, Markel; Oliveira, Rafael; Filipa Silva, Ana; Sarmento, Hugo; Afonso, José (Biology of Sport, 2022)
Small-sided games (SSGs) are widely used in soccer training. However, some of the typical outcomes related to human responses during these games (namely internal and external load) may vary between sessions for similar practice conditions. Thus, the study of intra- and inter-bout variability in response to SSGs is progressively growing. This systematic review aimed to (1) identify studies that have examined the intraand inter-session bouts’ variability levels regarding the internal and external load and technical/tactical outcomes during SSGs and (2) summarize the main evidence. A systematic review of PubMed, SPORTDiscus, Cochrane, and Web of Science databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. From the 486 studies initially identified, 24 were fully reviewed, and their outcome measures were extracted and analyzed. Sixteen studies analyzed internal load, 13 studies analyzed external load variables, six studies analyzed technical execution, and two studies analyzed tactical behavior. All studies included SSGs with a range number of players between 2 to 14 (1 vs. 1 to 7 vs. 7 SSGs). Internal load and low-speed external load variables presented a low variability, while high variations were reported regarding the technical execution and high-speed external loads.